(3OjhGf TYQ eLehYs
(3ChdgG (B:s
(3hHYO(B: (3abO SCdfj HYV ENhGfj Cf CLeY eLehYkG dWjakG XQjakG ef cdGe Gdbhe hZjQge ef GdYTGb hGodeMHjf djchf YeOI dcd hGba Ydjg ef TGYQ hcGJH ef GdbUGFO s
(3BNQgG (B:s
(3jGfG YSj GdWQa Lafj ajc jbXGf hjGaDGOj aDGOj efc edGf hBNQgG(B: (3hcja jNVQ BS aj YhGQVg hahb hLfJg GdMeQGA fjQGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B135 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs